Event-stanbul? Contemporary Istanbul as a Site of Intersecting Urban Events. Issue 3 (26th May 2020) - Houston, Christopher
ABSTRACT: Are there contingent urban events that are not the inevitable or determined outcome of other happenings or incidents, and yet transform the present city and exert their force and influence into the future? If so, how do we identify and explicate them? This paper describes three urban events in Istanbul that became significant determining acts in the city's modern period, co-constituting both the morphology of the city, the experiences of its inhabitants, and its ethnic/religious composition. Kemalist de-Ottomanization of the city via policies of Turkification after 1923; modernist urban planning; and the spatial activism of revolutionary movements in the late 1970s: each urban event became a source of novel spatial arrangements, new social divisions, and altered perceptions and memories of the city. Exploration of them shows that urban events entangle to part-assemble the contemporary city, yet their creative dynamics do not coalesce to produce a coherent urban system.